Transaksi Fiktif Melalui Marketplace Daring Memanfaatkan Promo Cashback - Christian Tarapul Anjur Hasiholan; Anton Hendrik Samudra (Fakultas Hukum Universitas Surabaya, 2020)
The present development of technology, mainly with the presence of internet has presented new ways and opportunities in business, namely by electronic commerce (e-commerce). Despite having positive impact, e-commerce also has the potential to cause a negative impact, that is by cyber crime. This research is intended to analyse the possibility of a new cyber crime mode which utilizes cashback promotion in e-marketplace (mainly known as marketplace). The mode used by the perpetrators is to make fictitious transaction in order for the system of marketplace to provide many cashback promos for each transaction made. The perpetrators are allowed to do this mode because they take advantage of the flaw in the system of the marketplace due to the availability of the cashback promo for all of the consumer. The emergence of the possibility of a new cyber crime mode shows the importance of this case to be assessed based on The Law of Republic Indonesia Number 19 of 2016 Concerning Amandment to The Law of Republic Indonesia Number 11 Number 11 of 2008 concerning Electronic Information and Transactions when a transaction is considered as manipulative.